Academic freedom: can education resist the assault? - Shields, Carolyn M. (Frontiers in Education, 2025)
Academic freedom has experienced a long and sometimes difficult trajectory to achieve its present position in the 21st Century world. In fact, the question of whether education is a tool of the state or independent from political influence has long been with us. Should the university, or education in general promote orthodoxy or should it encourage free speech? This paper discusses the current state of academic freedom in educational organizations, focusing specifically on attacks against diversity, equity, and inclusion (DEI) in the United States. It discusses briefly, the arguments against DEI, as well as its benefits. It then suggests that transformative leadership may offer guidelines for a leadership response. In general, the response will need to foreground diversity and equity, acknowledge the historical barriers to the full inclusion and participation of everyone, and address mindsets as well as actions. Amidst the current backlash, leaders will require a considerable amount of moral courage to speak loudly and truthfully in order to truly be transformative.